Studying Kinetic and Thermodynamic Parameters of the Interaction of Ceftriaxone with Albumin Extracted from Healthy and Covid-19 Plasma - Wejdan Wadi Badi, Wadhah Naji. Al Sieadi, Thikra Hasan Mathkor (Pakistan Journal of Medical & Health Sciences, 2022)
Because it has been well defined, bovine serum albumin (BSA) is highly suited to pharmacological effects, biotransformation, and bio-distribution of medicines initial research. Drug–protein interactions in the blood stream are known to have a significant impact on drug distribution, free concentration, and metabolism. Coronavirus disease 2019 (COVID-19) has spread globally as a severe pandemic. It is a serious threat to healthcare systems, economies, and is devastating to some populations, such as the elderly and those with comorbidities. Unfortunately, there is still no effective cure for COVID-19, especially the critically ill patients. The link between the mortality risk of patients hospitalized for COVID-19 and the function of blood albumin levels has been investigated. Because of albumin biological significance, the study goal conducted to apply spectroscopic methods to explore and comparing the kinetic and thermodynamic aspects of ceftriaxone’s interaction with BSA, albumin isolated from healthy and covid-19 plasma. A pooled plasma from healthy and hospitalized covid-19 individuals (Karbala Province / Iraq) was used to purify albumin using HPLC technique. UV-vis spectrophotometric measurements of albumin‒ceftriaxone complex formation recorded at different pH ( 7, 7.2, 7.4, 7.6 & 7.8) in phosphate buffer solution, and at six different temperatures (298, 301, 304, 307, 310 & 313) K. The equilibrium constant and the thermodynamic parameter such as ΔG, ΔH and ΔS were calculated. The drug-albumin (BSA, healthy and Covid-19 albumin) complexes are stable in 60 to 300 minutes, as evidenced by the steady absorbance studies. The reaction is from the first false order for drug-albumin (BSA, healthy and covid-19 plasma) complexes. Our finding suggesting the reaction is from the first false order. In the case of plasma albumin from individuals infected with - Covid-19, the values of (R2) are closer together. This is because the medication dominates the formation of a more stable complex with albumin. The stoichiometric ratio (coordination number) of complex between ceftriaxone and albumin at 298 k and pH=7.4 is 1:1. The Gibbs free energy for albumin‒ ceftriaxone is negative, indicating that the reaction is spontaneous. The positive enthalpy of contact indicates that the process is endothermic, requiring energy input. Positive enthalpy and entropy change also refer to the hydrophobic association and electrostatic contact that occurs between albumin molecules and ceftriaxone. It is worth noting that the complex formed between bovine albumin and the medication has less absorbency at pH = 7.4. That is, the complex is more stable, and it prefers natural helical shapes. Additionally, as the pH value shifts away from physiological (> 7.4 <), the intensity of complex absorption increases.